Omics Approach to Manage Abiotic Stress in Cereals - Roychoudhury, Aryadeep; Aftab, Tariq; Acharya, Krishnendu (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The edited book highlights various emerging Omics tools and techniques that are currently being used in the analysis of responses to different abiotic stress in agronomically important cereals and their applications in enhancing tolerance mechanism. Plants are severely challenged by diverse abiotic stress factors such as low water availability (drought), excess water (flooding/ waterlogging), extremes of temperatures (cold, chilling, frost, and heat), salinity, mineral deficiency, and heavy metal toxicity. Agronomically important cereal crops like Rice, Wheat, Maize, Sorghum, Pearl Millet, Barley, Oats, Rye, Foxtail Millets etc. that are the major sources of food material and nutritional components for human health are mostly exposed to abiotic stresses during the critical phases of flowering and grain yield. Different Omics platforms like genomics, transcriptomics proteomics, metabolomics and phenomics, in conjunction with breeding and transgenic technology, and high throughput technologies like next generation sequencing, epigenomics, genome editing and CRISPR-Cas technology have emerged altogether in understanding abiotic stress response and strengthening defense and tolerance mechanism of different cereals. This book is beneficial to different universities and research institutes working with different cereal crops in the areas of stress physiology, stress-associated genes and proteins, genomics, proteomics, genetic engineering, and other fields of molecular plant physiology. The book can also be used as advanced textbook for the course work of research and master's level students. It will be of use to people involved in ecological studies and sustainable agriculture. The proposed book bring together the global leaders working on environmental stress in different cereal crops and motivate scientists to explore new horizons in the relevant areas of research.
Chapter 1. Morphological, architectural and biochemical modifications of cereal crops during abiotic stress -- Chapter 2. Cereal physiology, flowering and grain yield under salinity and drought stress -- Chapter 3. Physiology, flowering and grain yield under abiotic stress imposed by heavy metals -- Chapter 4. Priming effect in developing abiotic stress tolerance in cereals through metabolome reprograming -- Chapter 5. Understanding abiotic stress tolerance in cereals through genomics and proteomics approaches -- Chapter 6. Metabolome analyses in response to diverse abiotic stress -- Chapter 7. Metabolomic profiling of different cereals during biotic and abiotic stresses -- Chapter 8. Plant breeding strategies for abiotic stress tolerance in cereals -- Chapter 9. Transgenic strategies to develop abiotic stress tolerance in cereals -- Chapter 10. Genetically engineered cereals tolerant to abiotic stress -- Chapter 11. Genome editing and CRISPR-Cas technology for enhancing abiotic stress tolerance in cereals -- Chapter 12. Abiotic stress tolerance in cereals through genome editing -- Chapter 13. Varietal physiology, metabolic regulation and molecular responses of rice genotypes to diverse environmental stresses -- Chapter 14. Breeding and Omics Approaches to Understand Abiotic Stress Response in Rice -- Chapter 15. Genomics and transcriptomics approaches to understand abiotic stress response in rice -- Chapter 16. Biochemical and molecular mechanism of wheat to diverse environmental stresses -- Chapter 17. How microRNAs Regulate Abiotic Stress Tolerance in Wheat? A Snapshot -- Chapter 18. Molecular-genetic studies, breeding and genomics-based approaches to develop abiotic stress tolerance in sorghum -- Chapter 19. MicroRNAs shape the Tolerance Mechanisms against Abiotic Stress in Maize -- Chapter 20. Transcriptome, proteome and metabolome profiling for abiotic stress tolerance in maize and barley -- Chapter 21. Omics tools to understand abiotic stress response and adaptation in rye, oat and barley -- Chapter 22. Genomic tools and proteomic determinants for abiotic stress tolerance in pearl millet (Pennisetum glaucum) and foxtail millet (Setaria italica L.) -- Chapter 23. Advancement in Omics Technologies for Enhancing Abiotic Stress Tolerance in Finger millet -- Chapter 24. Buckwheat (Fagopyrum esculentum) response and tolerance to abiotic stress -- Chapter 25. Abiotic Stress Response and Adoption of Triticale.
Keywords: Stress (Physiology).; Plants; Plant physiology; Plant biotechnology; Plant genetics; Plant Stress Responses; Plant Physiology; Plant Biotechnology; Plant Genetics